Chronic venous insufficiency – epidemiology, classification and clinical picture. Diagnostic and therapeutic recommendations of the Polish Dermatological Society. Part I - Narbutt, Joanna; Bowszyc-Dmochowska, Monika; Kapińska-Mrowiecka, Monika; Kaszuba, Andrzej; Krasowska, Dorota; Kręcisz, Beata; Lesiak, Aleksandra; Lis-Święty, Anna; Maj, Joanna; Nowicki, Roman; Owczarek, Witold; Placek, Waldemar; et al. (Dermatology Review/Przegląd Dermatologiczny, 2018)
Chronic venous insufficiency is an important clinical problem in daily dermatological practice. The disease is caused by impaired function of the venous system in the lower limbs and affects approximately 60% of the adult population. The article discusses the key epidemiological factors of chronic venous insufficiency, the updated classification and the clinical features of skin lesions developing in the course of the disease.